2021
DOI: 10.3390/foods10040822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, Added Calcium and pH on the Equilibrium of Caseins between Micellar State and Milk Serum

Abstract: Micellar casein and casein monomers in milk serum are in a dynamic equilibrium. At temperature below 15–20 °C a considerable amount of casein monomers, β-casein in particular, is released from the casein micelle into the aqueous serum phase. This study investigates the effects of added calcium and related variations of pH on this peculiar equilibrium in order to minimize the amount of caseins in the serum and to better understand the casein permeation during microfiltration. The pH was varied in the range of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Lowering the pH from 7.0 to 5.2 shortens the RCT, with the optimal pH for hydrolysis of κ-casein in the range of 5.1-5.3 [2,4]. The most important effects of lowering the pH of milk are the dissolving of micellar calcium phosphate, reduction in the net charge of the casein as well as dissociation of caseins from micelles [3,10]. Additionally, it has been reported that limited pH lowering leads to an increase in the gel firming rate [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lowering the pH from 7.0 to 5.2 shortens the RCT, with the optimal pH for hydrolysis of κ-casein in the range of 5.1-5.3 [2,4]. The most important effects of lowering the pH of milk are the dissolving of micellar calcium phosphate, reduction in the net charge of the casein as well as dissociation of caseins from micelles [3,10]. Additionally, it has been reported that limited pH lowering leads to an increase in the gel firming rate [11].…”
Section: Introductionmentioning
confidence: 99%
“…It provides stability to the system as calcium binds to casein phosphoprotein is pH‐dependent and generally binds at pH 7 or above. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib-loaded casein nanoparticles (SFN-CasNPs) were prepared according to our previously reported method [18] and further optimized to improve their drug encapsulation efficiency. Briefly, 200 µL of methanolic solution of sorafenib (1 mg mL (20,30,40,50) µL (Table 3) was added as a crosslinker and for the formation of casein nanoparticles. It was kept on a magnetic stirrer for evaporation of the organic solvent.…”
Section: Synthesis Of Casein Nanoparticlesmentioning
confidence: 99%
“…The natural variation in milk pH was found to affect cheese composition, i.e., cheeses manufactured from milk with a relatively low pH at renneting had less protein (P < 0.05) (Fig. 1C), an effect that may ensue from a greater displacement of micellar casein to the whey (Schiffer, Scheidler, Kiefer & Kulozik, 2021). In addition, cheeses made from curd that was drained/milled at a relatively low pH, had lower DM (P < 0.05) (Figs.…”
Section: Relationships Between Cheese Manufacturing Conditions and Ch...mentioning
confidence: 99%